A Framework for Integrating Arts, Science, and Social Justice Into Culturally Responsive Public Health Communication and Innovation Designs. (May 2021) - Edmonds, Theo; Drake, Hannah; Miller, Josh; Trabue, Nachand; Lister, Cameron; Salunkhe, Sonali S.; O'Keefe, Molly; Alzahrani, Sahal; White, Kelsey; Levinson, Amanda
Objectives . To increase the scale and efficacy of health promotion practice, culturally responsive approaches to well-being are needed in both communication and practice innovation. This mixed-methods evaluation sought to identify specific mechanisms used in a promising practice model and offers a potential theoretical framework to support public health programs in integrating culture and social justice into communication and intervention programs. Study Design . Rooted at the intersection of ethnographic and phenomenological worldviews, this mixed-methods, retrospective process evaluation used publicly available empirical and experiential data centered on the arts, science, and social justice to identify critical mechanisms used and incorporate them into an emergent theoretical framework. Method . The retrospective process evaluation used an ethnography-informed approach combined with scientific literature reviews. To integrate adjacent ideas into the emergent theoretical framework, a phenomenologically informed theme development approach was used. Results . The evaluation resulted in a five-step framework, called MOTIF, with the potential to be utilized in diverse situational and geographic contexts. Data that surfaced from related literature reviews revealed adjacent mechanisms from positive psychology, critical consciousness theory, and innovation design that were incorporated into the emergent framework. Conclusion . MOTIF may offer a culturally responsive public health communication and innovation process capable of promoting health equity through the cultivation of relationships between artists, community participants, and public health agencies and researchers who collectively endeavor to craft innovative solutions for population health and well-being.